SUPERVISION FOR NURSING DOCUMENTATION IN AN INDONESIAN PSYCHIATRIC HOSPITALS - Ramadhansyah Purnomo Iswa; Marthoenis; Mudatsir (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Background: Nurses are among the largest providers in the health care system. Nurses play an important role in improving the quality of hospital services, especially in nursing documentation, to record patient information clearly and ensure it can be accounted for as set standards. Materials and Methods: This cross-sectional study was conducted among 99 nurses at a mental hospital in Indonesia. The sample is selected by convenience sampling. Data was collected using supervision questionnaires and their socio demographic information. Data were analyzed using frequency distribution. Result: The average age of respondents was 37.7 years; more than half had a Bachelor of nursing education and had worked in a hospital for about 10 years. Regarding supervision for nursing documentation, more than half perceived that it still need to be improved (66.7%), while the principle of supervision is mostly in the good category (75%), as well as supervision models (68%) and supervision activities (71.7%). Discussion: To maintain and improve the culture of nursing development, supervision from superiors and the routine of improving other colleagues in performing nursing documentation need to be enhanced.